Contradictory Impartiality Principle in the Supervisory System of Constitutional Court Judges - Ali Prakosa; Pompy Polansky Alanda; Nurul Istianah; Luthcas Rohman (Jurnal Cakrawala Hukum, 2019)
The Constitutional Court (MK) through Its Verdict No.  1-2 / PUU-XII / 2014 substantially causes a legal vacuum (rechtsvacum) serving as the basis for the constitutional judge's external supervisory body.  Besides that, with the application of the Constitutional Court's supervisory system through the Ethics Council and the Constitutional Court Honorary Council (MKMK) is considered to have deviated the principle of nemo judex idoneus in propria causa because one of the members of the MKMK was a constitutional judge, means hearing his own case.  The research method used is the normative legal research method with the statue approach and conceptual approach. Supervision of Constitutional Court judges requires Reinventing (legal reform) by involving members of the Supreme Court and members of the House of Representatives as members of the Ethics Council and replacing one Constitutional Judge with one former Supreme Court Judge.  The supervision change of the Constitutional Court judges is aimed to increase the authority of the Constitutional Court and to hold the principle of impartiality.How to cite item: Prakosa, A., Alanda, P., Istianah, N., Rohman, L. (2019). Contradictory Impartiality Principle in the Supervisory System of Constitutional Court Judges. Jurnal Cakrawala Hukum, 10(2), 117-125. doi:https://doi.org/10.26905/idjch.v10i2.3470